Enhance the routing QoS for multimedia streaming using two-hop information in mobile ad hoc networks. (15th July 2021) - Kumar, T. Sathish; Gopalan, N.P.; Rajesh, R.
The latest technology is a wireless network which comprises the lack of commercial infrastructure and the transparency in mobile ad hoc network and it provides quality of service (QoS) for multimedia streams when mobile nodes in static position. The existing routing protocol should communicate with a different protocol in MANETs environment, which are likely to move from an existing wireless network and to any networks. It gets an unreliable network topology and also allocates various channels to a mobility node, it performance does not create sufficient network resources, and also sometimes mobile nodes met issues. This paper proposes a two-hop neighbour detail-based directional route (THDR) routing, to provide QoS for multimedia streaming. THDR routing protocols believe the conditions of the equivalent properties. The main element of the proposed THDR protocol is the two-hop information delay assessment. The results of the execution conclude that THDR confirms the recommendations available on multimedia streams.